To Serve the People : My Life Organizing with Cesar Chavez and the Poor - Chatfield, LeRoy, 1934-; Mariscal, George (Book collections on Project MUSE., 2019)
"The long pilgrimage of LeRoy Chatfield weaves its way through multiple collective projects designed to better the condition of the marginalized and forgotten. From the cloisters of the Christian Brothers and the halls of secondary education to the fields of Central California and the streets of Sacramento, Chatfield's story reveals a fierce commitment to those who were denied the promises of the American dream. In this collection of what the author calls Easy Essays, Chatfield recounts his childhood, explains the social issues that have played a significant role in his life and work, and uncovers the lack of justice he saw all too frequently. His journey, alongside Cesar and Helen Chavez, Marshall Ganz, Bonnie Chatfield, Philip Vera Cruz, and countless others, displays an unwavering focus on organizing communities and expanding their agency. Follow and explore a life dedicated to equality of opportunity for all. May it inspire and guide you in your quest for a fairer and more just society"--